2017
DOI: 10.1038/cddis.2017.89
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant iPSC-derived human astrocytes in Alzheimer's disease

Abstract: The pathological potential of human astroglia in Alzheimer's disease (AD) was analysed in vitro using induced pluripotent stem cell (iPSC) technology. Here, we report development of a human iPSC-derived astrocyte model created from healthy individuals and patients with either early-onset familial AD (FAD) or the late-onset sporadic form of AD (SAD). Our chemically defined and highly efficient model provides >95% homogeneous populations of human astrocytes within 30 days of differentiation from cortical neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
139
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(143 citation statements)
references
References 48 publications
4
139
0
Order By: Relevance
“…Table shows some features of aberrant glial cells, including astrocytes or microglia, abnormally‐expressing markers from different cell lineages have been also reported in Alzheimer's disease, Huntington's disease, central nervous system acute lesions and aging, as well as glioma, brain ischemia and trauma, further suggesting the phenotypic switch is strongly associated with inflammation and tissue remodeling after damage.…”
Section: Phenotypic Heterogeneity Of Astrocytes In Als and Other Neurmentioning
confidence: 80%
“…Table shows some features of aberrant glial cells, including astrocytes or microglia, abnormally‐expressing markers from different cell lineages have been also reported in Alzheimer's disease, Huntington's disease, central nervous system acute lesions and aging, as well as glioma, brain ischemia and trauma, further suggesting the phenotypic switch is strongly associated with inflammation and tissue remodeling after damage.…”
Section: Phenotypic Heterogeneity Of Astrocytes In Als and Other Neurmentioning
confidence: 80%
“…Astrocytes associated with senile plaques display Ca 21 hyperexcitability and generate abnormal propagating intercellular Ca 21 waves. (104,118,129,170,201,202,204,261,264,267,273) Ageing-related tau astrogliopathy Exclusive expression of pathological tau in astrocytes is the sole histological symptom of several age-dependent dementias.…”
Section: Nosological Forms Astrocytopathy Referencesmentioning
confidence: 99%
“…Very recently, AD-associated astrocyte dysfunction has also been described in human iPSC-derived cell models. Using this model, atrophy of astrocytes and abnormal expression of astrocytic markers were demonstrated in iPSC-derived astrocytes from patients with familial and sporadic forms of AD [54]. We have also shown that iPSC-derived AD astrocytes are compromised in neuronal supportive function, and display increased β-amyloid production and oxidative stress, altered cytokine release, and dysregulated Ca2+ homeostasis [67].…”
Section: Astrocytes In Alzheimer's Diseasementioning
confidence: 83%
“…In addition to rodent models, recent advances in stem cell technologies have promoted the use of human-based cell models for AD research. For example, it is now possible to model AD in vitro by using induced pluripotent stem cells (iPSCs) and cells derived from these by differentiation [53][54][55].…”
Section: Astrocytes In Alzheimer's Diseasementioning
confidence: 99%